Analisis Yuridis tentang Penerapan Perlindungan Hukum terhadap Anak Sebagai Pelaku Tindak Pidana Pencabulan - Laeko Lapandewa; Arifandi Waikabo; Varissca Utari Tuharea (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2026)
Criminal law constitutes a part of the legal system that regulates prohibited acts and imposes sanctions on individuals who violate such prohibitions. From the perspective of national law, children are recognized as legal subjects who are entitled to legal protection as guaranteed under Article 28B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Nevertheless, in practice, some children become involved as perpetrators of criminal offenses, including sexual molestation offenses, thereby requiring legal handling through the Juvenile Criminal Justice System while still prioritizing the best interests of the child. This study aims to analyze the factors that encourage children to commit the criminal offense of sexual molestation and to examine the implementation of legal protection for children who commit such offenses. The research employs a normative legal research method with a library research approach, relying on secondary data derived from legislation, books, scholarly journals, and other legal documents. The results indicate that the factors contributing to children committing the offense of sexual molestation consist of external and internal factors. External factors include the family environment, school environment, community conditions, and negative peer associations. Internal factors include a lack of discipline and self-control, low self-confidence, feelings of neglect by the surrounding environment, the desire to obtain something instantly, and experiences of disappointment. Legal protection for child perpetrators of sexual molestation is regulated under Law Number 1 of 2023 concerning the Criminal Code, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Law Number 35 of 2014 concerning Child Protection, and Government Regulation Number 65 of 2015 concerning Guidelines for the Implementation of Diversion and the Handling of Children Under the Age of Twelve.